Reaching Millennials: Implications for Advertisers of Competitive Sporting Events that Use Animals - Jackie Hill; Mallory Mobly; Billy R. McKim (Journal of Applied Communications, 2016)
The purpose of this mixed method, multi-modal case study was to identify the most acceptable video images of animals to use when advertising competitive sporting events. Data were collected from college students at Arizona State University, California State University-Fresno, Texas A&M University, University of California-Berkeley, University of California-San Diego, and University of Texas. We investigated which sporting events are most acceptable among members of the Millennial generation, if there were differences in responses based on Millennials’ gender, and if perceptions differed among rodeo and non-rodeo events. Based on our results, gender did not influence Millennials’ perceptions of the use and treatment of animals in the 16 competitive sporting events presented in this study. However, non-rodeo events were perceived more positively than rodeo events. Of the eight rodeo events, respondents perceived barrel racing as most acceptable and the event in which the animal was treated most kindly. Respondents perceived team roping as least acceptable and the event in which the animals were treated least kindly. The results of this study include strategies that may improve advertising rodeo and non-rodeo events to Millennials by selecting images that are most acceptable to Millennials and considerations for reaching target audiences.
Keywords: Advertising; Animal Welfare; Rodeo; Social Cognitive Theory; Sports